2011
DOI: 10.1111/j.1365-246x.2011.05018.x
|View full text |Cite
|
Sign up to set email alerts
|

Hellenic Unified Seismological Network: an evaluation of its performance through SNES method

Abstract: S U M M A R YIn this paper, we analyse the location performance of the Hellenic (Greek) Unified Seismological Network (HUSN) by Seismic Network Evaluation through Simulation method (SNES). This method gives, as a function of magnitude, hypocentral depth and confidence level, the spatial distribution of the: number of active stations in the location procedure and their relative azimuthal gaps and confidence intervals in hypocentral parameters regarding both the geometry of the seismic network and the use of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…These findings is in good agreement with the studies [6,23], which analyzed the location performance of the HUSN network by numerical simulation of the detecting earthquakes.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These findings is in good agreement with the studies [6,23], which analyzed the location performance of the HUSN network by numerical simulation of the detecting earthquakes.…”
Section: Discussionsupporting
confidence: 82%
“…Parameters According to the HUSN Earthquakes Catalogue The reliability of these finding is supported by the coincidence of the results for the location performance of stations HUSN [23,6]. In these studies showed that for the major part of Greek territory Mc = 2,0.…”
Section: Spatial Pattern Of Seismicitysupporting
confidence: 56%
See 2 more Smart Citations
“…As well known, the magnitude detection threshold and location performance of a seismic network are mainly related to the noise level and geometry of the stations that make up the network (D'Alessandro et al, 2011a(D'Alessandro et al, , b, 2012b(D'Alessandro et al, , 2013bD'Alessandro and Stickney, 2012;D'Alessandro and Ruppert, 2012;D'Alessandro and D'Anna, 2013). OBS are increasingly used to monitoring offshore areas while downhole sensors always have been used to reduce natural noise level.…”
Section: Discussionmentioning
confidence: 99%